2012
DOI: 10.1104/pp.112.202358
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones Are Involved in Root Response to Low Phosphate Conditions in Arabidopsis  

Abstract: Strigolactones (SLs) are plant hormones that suppress lateral shoot branching, and act to regulate root hair elongation and lateral root formation. Here, we show that SLs are regulators of plant perception of or response to low inorganic phosphate (Pi) conditions. This regulation is mediated by MORE AXILLARY GROWTH2 (MAX2) and correlated with transcriptional induction of the auxin receptor TRANSPORT INHIBITOR RESPONSE1 (TIR1). Mutants of SL signaling (max2-1) or biosynthesis (max4-1) showed reduced response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
166
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 204 publications
(176 citation statements)
references
References 57 publications
(96 reference statements)
9
166
1
Order By: Relevance
“…However, little has been reported on the effect of nutrient deficiency and root hair length, which seems to be the aspect of root hair development most affected by strigolactones. However, it has been suggested that the root hair response to low Pi is mediated by strigolactones and could be correlated with transcriptional activation of TIR1, thus complementing the experimental evidence that auxin is sufficient to compensate for the reduced max2 responses (Mayzlish-Gati et al 2012). …”
Section: Root Hair Length Is Enhanced By Strigolactonesmentioning
confidence: 81%
See 1 more Smart Citation
“…However, little has been reported on the effect of nutrient deficiency and root hair length, which seems to be the aspect of root hair development most affected by strigolactones. However, it has been suggested that the root hair response to low Pi is mediated by strigolactones and could be correlated with transcriptional activation of TIR1, thus complementing the experimental evidence that auxin is sufficient to compensate for the reduced max2 responses (Mayzlish-Gati et al 2012). …”
Section: Root Hair Length Is Enhanced By Strigolactonesmentioning
confidence: 81%
“…In contrast to lateral root formation, Pi-deficient inhibition of root growth occurs independently of strigolactone signaling, as evidenced by Pi-deficient inhibition of primary root growth in both max2 and wild type (Yoneyama et al 2007;Jain et al 2007;Mayzlish-Gati et al 2012).…”
Section: Strigolactones Increase Primary Root Lengthmentioning
confidence: 99%
“…Moreover, abamineSG, which decreases SL levels in plants, reduced the response to low P in wild-type, but not in SL mutant, plants. 22 Interestingly, several lines of evidence suggest that SLs are involved in rice root growth in response to N and P deficiencies. 3,4 The application of GR24 to wild-type plants and SL synthetic mutants, but not signaling mutants (d3), under nutrientsufficient conditions led to the complete recovery of seminal root length and LR density compared to wild-type plants under Nand P-deficient conditions.…”
Section: Strigolactones (Sls) Regulate Root Developmentmentioning
confidence: 99%
“…14,[16][17][18][19][20][21] Recently, it was reported that SLs regulate the perception or response of plants to P-limited conditions. 22 In Arabidopsis, mutants of SL signaling (max2-1) and biosynthesis (max4-1) showed reduced responses to P-limited conditions relative to wild-type plants. In max4-1, but not max2-1, the reduced response to low P was compensated by GR24 application.…”
Section: Strigolactones (Sls) Regulate Root Developmentmentioning
confidence: 99%
See 1 more Smart Citation